THE DEVELOPMENT OF GUILDFORD DUDLEY’S SELF-CONCEPT AS AN ETHIAN IN MY LADY JANE (2024) - Artamia, Mayang Dyah (Universitas Negeri Surabaya, 2025)
Self-concept refers to an individual’s perceptions and beliefs about themselves. It has a significant influence on an individual’s personality and behavior, which in turn affects the way they form social relationships. In My Lady Jane (2024), the people are divided into two groups: regular human beings called Verities and a group of people who can transform into animals called Ethians. This study aims to explore the portrayal of Guildford Dudley’s self-concept development as an Ethian and how it affects his romantic relationship with a Verity named Jane Grey. By using a film analysis approach, this study utilizes subtitles as the main data and scenes screenshots as supporting data. This study employs Carl Rogers’ theory of self-concept (1959) to reveal how My Lady Jane (2024) portrays Guildford Dudley’s self-concept as a journey toward self-acceptance. This study also reveals how Guildford Dudley’s self-concept as an Ethian leads his relationship with Jane Grey through every stage and at the same time is affected by it.